2016
DOI: 10.2169/internalmedicine.55.5196
|View full text |Cite
|
Sign up to set email alerts
|

The Long-term Effect of Adrenal Arterial Embolization for Unilateral Primary Aldosteronism on Cardiorenovascular Protection, Blood Pressure, and the Endocrinological Profile

Abstract: Primary aldosteronism (PA) is a major cause of secondary hypertension, divided into two subtypes: unilateral and bilateral. Unilateral PA (u-PA) is surgically-curable. Medical treatment with mineralocorticoid receptors antagonists is recommended as a second-line treatment when the patients are not candidate for surgical treatment. The present case was a 39-year-old woman with u-PA, who had refused surgery, had suffered from adverse effects of medical treatment. She was treated with transcatheter adrenal arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…If AH leads to hemodynamic instability, emergency resection of the affected adrenal gland will be required. If surgery cannot be conducted promptly, trans-catheter adrenal arterial embolization [ 22 ], which is a treatment option for unilateral PA, may be effective for AH.…”
Section: Discussionmentioning
confidence: 99%
“…If AH leads to hemodynamic instability, emergency resection of the affected adrenal gland will be required. If surgery cannot be conducted promptly, trans-catheter adrenal arterial embolization [ 22 ], which is a treatment option for unilateral PA, may be effective for AH.…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al in 1993, who, with other research centers, reported encouraging long-term results [8][9][10]16. Hokotate et al reported 33 cases of APA treated by SAAE, with a mean follow-up duration of 45 months 10.…”
mentioning
confidence: 99%